2015
DOI: 10.18034/abr.v2i1.309
|View full text |Cite
|
Sign up to set email alerts
|

Traffic Congestion in Bangladesh- Causes and Solutions: A study of Chittagong Metropolitan City

Abstract: One of the most challenging and complicated issues in city management in the present decade for Bangladesh is the traffic problem. It is a very common phenomenon in almost all the cities of Bangladesh. Presently, traffic congestion problem in Bangladesh are increasing at an alarming rate. The traffic problem has become to a very dangerous arena and has already implicit agonizing extent in the cities of Bangladesh. This type of study has been conducted in Dhaka but not in Chittagong city. Traffic management in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 2 publications
(2 reference statements)
0
5
0
Order By: Relevance
“…Also the impact of time delay, economy and pollution had been discussed [24] indicated that the increase in economic growth and the increase in population in Nigeria have led to an increase in traffic congestion, also due to the increase in accidents on the roads and the ease of obtaining driving licenses for young people of 15 years [25]. Shamsher and Abdullah (2013) indicated that among the main causes of traffic jams in Bangladesh is the lack of adequate parking spaces for vehicles, and this is what forces vehicles to stop on the side of the road in addition to the limited availability of buses and poor road infrastructure [26]. Revenio C. J. and Almalinda M. J.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also the impact of time delay, economy and pollution had been discussed [24] indicated that the increase in economic growth and the increase in population in Nigeria have led to an increase in traffic congestion, also due to the increase in accidents on the roads and the ease of obtaining driving licenses for young people of 15 years [25]. Shamsher and Abdullah (2013) indicated that among the main causes of traffic jams in Bangladesh is the lack of adequate parking spaces for vehicles, and this is what forces vehicles to stop on the side of the road in addition to the limited availability of buses and poor road infrastructure [26]. Revenio C. J. and Almalinda M. J.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The most serious air pollution is caused by automobile emissions as the number of registered vehicles in Chittagong city reached 84,391 in 2010, which does not include several thousands of non-registered vehicles (Shamsher & Abdullah, 2012). There is then the pollution from brick kilns and industrial emissions, such as from the ship breaking industry (Sujauddin et al, 2014), which releases the pollutants of asbestos and polychlorinated biphenyl (PCB) (Islam & Hossain, 1986).…”
Section: Environmental Issuementioning
confidence: 99%
“…Traffic jam has become a significant societal issue in contemporary life, affecting economic development and environmental pollution [1][2][3][4][5]. Many researchers have established various models, such as car-following, cellular automaton, gas kinetic, and hydrodynamic models, to reproduce the actual traffic flow better and explore the sociophysics mechanisms behind complex traffic phenomena [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%